Association of antihypertensive drugs with COVID-19 outcomes: a drug-target Mendelian randomization study - Zhang, Kun; Gao, Hengxing; Chen, Mingwei (Frontiers in Pharmacology, 2023)
Background: Observational investigations have provided conflicting results regarding the effect of antihypertensive drugs on the risk of COVID-19 outcomes. We intended to assess the causal effect of antihypertensive drugs on COVID-19 outcomes using drug-target mendelian Mendelian randomization (MR), mainly including angiotensin-converting enzyme inhibitors (ACEIs), βblockers (BBs) and calcium channel blockers (CCBs).Methods: We used the genetic variants (minor allele frequency > 1%, r 2 < 0.30) located within 100k bases of each drug target gene and associated with lower systolic blood pressure (P < 5×10 -8 ) as genetic proxies for antihypertensive drugs. COVID-19 outcomes included COVID-19 susceptibility (122,616 cases and 2,475,240 controls), hospitalization (32,519 cases and 206,2805 controls), and severe illness (13,769 cases and 1,072,442 controls). All studies were conducted on populations of European ancestry. MR estimates were generated using an inverse-variance weighted (IVW) model.Results: IVW-MR analysis observed a weak causality between CCBs and COVID-19 susceptibility (OR: 0.993, 95% CI: 0.988-0.999, P = 0.012). Sensitivity analysis suggested that this result was robust. No evidence was found for a link between other antihypertensive drugs and COVID-19 outcomes.The present study suggests that CCBs may reduce COVID-19 susceptibility in European populations.